DIGITAL MEDIA PRACTICES IN MUSLIM FAMILIES IN YOGYAKARTA : A MASLAHAH AND SADD AL-DHARĀ’I ANALYSIS OF FAMILY INTERACTION - Susiana; Hasmia Wahyunisa; Neneng Desi Susanti; Fathur Baldan Haramain (Program Studi Hukum Keluarga Fakultas Syariah UIN Datokarama Palu, 2026)
This study examines digital media practices among Muslim families in Yogyakarta through the perspectives of maṣlaḥah and Sadd al-dharā’iʿ in maintaining the quality of family interaction in the digital era. Employing a qualitative case study approach, the research involved five Muslim families who actively utilize digital media in their daily lives. Data were collected through in-depth interviews, observations, and documentation, and analyzed thematically to explore how families benefit from digital media while managing its potential risks. The findings reveal that digital media is not understood dichotomously as either entirely beneficial or harmful, but rather as a practice continuously negotiated within family life. Maṣlaḥah is reflected in the use of digital media to sustain communication, support educational activities, and strengthen religious engagement. Meanwhile, Sadd al-dharā’iʿ is manifested through situational forms of regulation, including screen-time management, parental guidance, content supervision, and the development of digital communication ethics within the family. The study further finds that the relationship between maṣlaḥah and Sadd al-dharā’iʿ does not constitute a fixed balance; instead, it is better understood as a dynamic spectrum in which each family occupies a different position according to its experiences, priorities, and social context. Therefore, a sakinah family in the digital era is not defined as an idealized harmonious condition, but rather as the family’s capacity to manage relationships adaptively amidst the opportunities and risks of digital media use.